History of a Western Anatolian region - Arıkan, Fatma Melek, author.
1 online resource (xxi, 268 pages)
Keywords: "This volume is a local history, focusing on experiences of people and communities as they navigated and enacted institutions and transformations associated with modernization in the late Ottoman era. Focusing on the local political arena of a relatively small, predominantly rural and ordinary setting, the book examines two neighbouring Western Anatolian towns, Yenişehir and İznik. Utilising rigorous historiographical inquiry and in-depth usage of archival materials, this study sketches a dynamic picture of late Ottoman imperial political belonging with the agendas and priorities of the countryside, where the majority of Ottomans principally lived. The monograph contributes to interrogating modernization from different local perspectives by excavating the provincial hinterland of the imperial capital. It uses a narrative technique of analyzing certain local events for addressing larger structures and transformations pertaining to the long 19th century in general and Ottoman history in particular. As a "micro"-study, it argues for the significance of individuals' and social groups' agencies, strategies, and conceptions of their world in the unfolding of Ottoman modernization. Offering a vivid picture of local communities and their engagements with modern political, social and judicial structures in the late Ottoman era, this book will appeal to scholars and advanced graduate students, interested in comparative imperial history, Ottoman history and Middle Eastern studies"--